2004
DOI: 10.1158/1078-0432.ccr-1160-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Rituximab Does Not Inhibit the Human Immune Response against the Immunogenic Protein LMB-1

Abstract: Purpose: Rituximab, a humanized monoclonal antibody directed to the CD20 antigen present on B lymphocytes, could potentially abrogate the humoral immune response to murine monoclonal antibodies or immunotoxins by depleting antibody-producing B cells.Experimental Design: A Phase II study of LMB-1, an immunotoxin targeting the Lewis Y tumor antigen, in combination with rituximab was conducted to test the hypothesis that rituximab could abolish or diminish the development of human antibodies to LMB-1. Five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 16 publications
0
33
1
Order By: Relevance
“…Suppression of antibody response by rituximab was also examined. All patients had undetectable peripheral B cells when immunotoxin was administered but developed antiimmunotoxin antibodies despite this [33].…”
Section: Immunogenicitymentioning
confidence: 99%
“…Suppression of antibody response by rituximab was also examined. All patients had undetectable peripheral B cells when immunotoxin was administered but developed antiimmunotoxin antibodies despite this [33].…”
Section: Immunogenicitymentioning
confidence: 99%
“…One example of an accelerated administration schedule that increases the duration and amount of drug exposure before host development of neutralizing antibodies have being explored. [19][20][21][22] Efforts were also made to produce immunotoxins in mammalian cells so that they will have proper post-translational modifications that may potentially reduce their immunogenicity in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting solid tumours with ligand-directed cytotoxins has been hampered by problems with immunogenicity as effective therapy often requires multiple treatments resulting in the generation of neutralising antibodies, mostly against the PE38 portion of the molecule (Hassan et al, 2004). A potential solution to this problem was recently published by Onda and Pastan who showed that there are only seven major B-cell epitopes on the PE38 molecule ).…”
mentioning
confidence: 99%